Driving and Passing Skills Analysis in Futsal Games for Students Bumi Batara Mawang Futsal Academy Gowa District Permai - Sarifuddin Arham; Ikadarny Ikadarny (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This research is a descriptive analysis research with a categorization design that aims to describe the skills of herding and passing of students at the Bumi Batara Mawang Permai futsal academy, Gowa Regency. The population in this study were 75 students of the Bumi Batara Mawang Permai futsal academy, Gowa Regency. While the sample in this study were 30 core players from Bumi Batara Mawang Permai futsal academy students, Gowa Regency. The data collection techniques obtained through tests and measurements. The data analysis technique used is proportion and analysis. In this study, the results were obtained, namely the ability to dribble and pass the students of the Bumi Batara Mawang Permai Futsal Academy in Gowa Regency who often took part in training.